2023
DOI: 10.3390/vehicles5030056
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of a Driver’s Lumped Parameter Model in the Evaluation of Ride Comfort

Dimitrios Koulocheris,
Clio Vossou

Abstract: The ride comfort provided by a vehicle to the driver and the passengers is an important feature, directly correlated to the technical characteristics of the suspension system of the vehicle. In the literature, several lumped-parameter models simulating the vehicle and the driver are proposed for the computational evaluation of ride comfort. In order to quantify ride comfort, other than the values of acceleration, metrics such as seat effective amplitude transmissibility (SEAT) and seat-to-head transmissibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The section examines objective and subjective measurements of ride comfort that will explore many approaches used to evaluate the quality of a vehicle's ride experience. Objective metrics refer to quantitative measures, including frequency response analysis, displacement, acceleration, and velocity assessments [21], [22]. These data provide technical insights into the physical functioning of the suspension system.…”
Section: Objective and Subjective Metricsmentioning
confidence: 99%
“…The section examines objective and subjective measurements of ride comfort that will explore many approaches used to evaluate the quality of a vehicle's ride experience. Objective metrics refer to quantitative measures, including frequency response analysis, displacement, acceleration, and velocity assessments [21], [22]. These data provide technical insights into the physical functioning of the suspension system.…”
Section: Objective and Subjective Metricsmentioning
confidence: 99%
“…This functionality is achieved by enabling the control of the temperature differential between the evaporator and the compensation chamber, as described in [20,21]. To implement it, a 1D thermo-hydraulic lumped parameter model mathematical model, as in [22][23][24][25][26][27][28][29][30], capable of predicting design and thermal performance, is necessary. This model should account for transient responses, complex interactions involving two-phase fluid flow, heat transfer, flow through porous structures, dry-out and priming phenomena, as well as condensation and evaporation within the loop heat pipe.…”
Section: Introductionmentioning
confidence: 99%
“…This paper, which aims to develop a 1D thermo-hydraulic lumped parameter model [22][23][24][25][26][27][28][29][30] for a loop heat pipe working as a heat switch, is organized as follows: Section 2 presents the mathematical model of the loop heat pipe working as a heat switch, Section 3 focuses on the dimensioning parameters, such as geometry and fluid properties, which are used in the simulations, and the corresponding results are presented in Section 4. Section 5 involves a discussion on the challenges and achievements from the proposed model.…”
Section: Introductionmentioning
confidence: 99%
“…Donghui et al [17] analyzed ride comfort according to age group and reported that at speeds of 30-70 km/h, child seats encounter greater acceleration, resulting in reduced comfort. Kobayashi et al [18] analyzed ride comfort according to posture; anthropometric accuracy was studied using a sitting human model through lumped parameters with 4 degrees of freedom. Jung et al [19] conducted research on improving regenerative braking efficiency in electric vehicles.…”
Section: Introduction 1background Of the Studymentioning
confidence: 99%